2021
DOI: 10.1016/j.eclinm.2021.100952
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Profile and asymptomatic bacteriuria among pregnant women in Africa: A systematic review and meta analysis

Abstract: Background: Different physiologic changes that occur during pregnancy, such as Hydroureter, dilatation of the renal pelvis, glycosuria and aminoaciduria, and low urine production predispose pregnant women for ascending urinary tract infection. Globally, 2% to 15% of the pregnant women have urinary tract infection without specific symptoms. Therefore, this study aimed to estimate the prevalence of asymptomatic bacteriuria (ABU) in pregnant women in Africa. Methods: Systematic search of published studies done on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
(86 reference statements)
0
4
1
4
Order By: Relevance
“…revealed variation in the prevalence with highest prevalence 22% in West Africa with heterogeneity index (I 2 ) of 98.34% ( P < 0.001) and the lowest prevalence 11% in North Africa. [ 69 ] The variation in our study was less as compared to the one conducted in Africa.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…revealed variation in the prevalence with highest prevalence 22% in West Africa with heterogeneity index (I 2 ) of 98.34% ( P < 0.001) and the lowest prevalence 11% in North Africa. [ 69 ] The variation in our study was less as compared to the one conducted in Africa.…”
Section: Discussioncontrasting
confidence: 52%
“…Meta-analysis that involved 15,108 pregnant Iranian women from mainly cross-sectional studies showed overall prevalence of ASB as 13% in Iran and Africa reported the prevalence of 11.1% (95% CI: 7.8, 14.4), which was comparable to the present study. [ 68 , 69 ]…”
Section: Discussionmentioning
confidence: 99%
“…Bakteriuria asimtomatik adalah kolonisasi bakteri yang persisten pada traktus urinarius tanpa gejala simtomatik atau klinis dengan ditemukannya bakteri >10 5 cfu/ml yang diambil dari sampel urin midstream (Awoke dkk., 2021). Pada ibu hamil terjadi perubahan anatomi, fisiologi serta penurunan sistem imun, sehingga sangat rentan untuk terjadinya bakteriuria asimtomatik, dan bisa berlanjut menjadi infeksi saluran kemih yang mempunyai gejala klinis (Azami dkk., 2019).…”
Section: Pendahuluanunclassified
“…Escherichia coli is the most prevalent pathogen, causing between 75% and 90% of bacteriuria in pregnant women (7)(8)(9). Additionally, pregnant women are considered vulnerable hosts for UTIs due to the physiological changes associated with pregnancy, leading to compromised immunity (4).…”
Section: Introductionmentioning
confidence: 99%